Correlation between tumor-infiltrating lymphocyte density and disease-free survival rate in basal cell carcinoma patients at Dr. Soetomo General Hospital, Surabaya - Batubara, Immanuel Van Donn; Susillo, Dwi Hari; Wibowo, Marjono Dwi (Edelweiss Applied Science and Technology, 2025)
Basal cell carcinoma has a high risk of recurrence and can be associated with other types of cancer linked to ultraviolet radiation, impacting clinical outcomes, increasing morbidity, and shortening Disease-Free Survival (DFS) rates. Tumor-infiltrating lymphocytes (TILs) are considered predictors of immune response that are useful in suppressing tumor growth by infiltrating tumor cells. TILs were used as a predictive factor in the survival rate of basal cell carcinoma, with the result that high density was a good marker of immune system activation around the tumor and was associated with better prognosis. This study employed a retrospective cohort observational analytic research design to correlate the density of TILs with the DFS rate of basal cell carcinoma patients who had undergone wide excision at Dr. Soetomo General Hospital Surabaya from January 2017 to December 2023, with a total sample of 40 patients. Among the 40 samples, a group with strong TILs density was identified from a total of 14 samples, with 9 samples (22.5%) having DFS ≥ 5 years. In the weak TILs density group, there were 26 samples, with 9 samples (22.5%) having DFS for 1 year, 7 samples (17.5%) having DFS for 2 years, and 8 samples (20%) having DFS for 3 years. The analysis of the correlation between TILs density and DFS found that the stronger the TILs density, the longer the DFS time (p value = 0.002, RR 1.683). There was a significant correlation between TILs density and disease-free survival in patients with basal cell carcinoma who had undergone wide excision and/or radiotherapy.